Woman in the wilderness : a story of survival, love & self-discovery in New Zealand - Lancewood, Miriam (Auckland, New Zealand ; Crows, NSW : Allen & Unwin, 2017)
AUTOBIOGRAPHY: GENERAL. Miriam is a young Dutch woman living a primitive, nomadic life in the heart of the mountains with her New Zealand husband. She lives simply in a tent or hut, and survives by hunting wild animals and foraging edible plants, relying on only minimal supplies. For the last six years she has lived this way, through all seasons, often cold, hungry and isolated in the bush. She loves her life and feels free, connected to the land, and happy. There's a lot of drama out there in the wild, and Miriam knows how to spin a good yarn. This is a gripping and engaging read reminiscent of both adventure writing like Wild and nature writing like H is for Hawk, and is perfect for anyone exploring the idea of living a more authentic, real life.
Keywords: Lancewood, Miriam; Lancewood, Peter; Wilderness survival -- New Zealand -- Biography; Dutch -- New Zealand -- Biography; Married people -- New Zealand -- Biography; Self-reliant living -- New Zealand -- Biography; Man-woman relationships -- New Zealand -- Biography; Survivalism -- New Zealand -- Biography; Wilderness areas -- New Zealand; New Zealand -- Biography